2015
DOI: 10.1371/journal.pone.0139376
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Molecular Characterization of Invasive Meningococcal Disease in Italy, 2008/09-2012/13

Abstract: BackgroundFollowing the introduction of meningococcal serogroup C conjugate vaccine in Italy in 2005, changes in the epidemiology of Invasive Meningococcal Disease (IMD) were expected. The study aims were to describe the epidemiological trend and to characterize the isolates collected during the period 2008/09-2012/13 by multilocus sequence typing (MLST). Data on laboratory confirmed meningococcal diseases from National Surveillance System of IMD were reported.MethodsPoisson regression models were used to esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…An accurate serotyping achieved by involving microbiologists allows calculating the CFR for singular meningococcal serogroups. [30][31][32] When MenB was considered alone in our analysis, the CFR was 16.4%, a figure similar to the one reported in the Italian paediatric population. 21 It is impossible to say whether any patients with IMD died before reaching hospital.…”
Section: Discussionsupporting
confidence: 76%
“…An accurate serotyping achieved by involving microbiologists allows calculating the CFR for singular meningococcal serogroups. [30][31][32] When MenB was considered alone in our analysis, the CFR was 16.4%, a figure similar to the one reported in the Italian paediatric population. 21 It is impossible to say whether any patients with IMD died before reaching hospital.…”
Section: Discussionsupporting
confidence: 76%
“…A total of 30 studies reported impact of MCCV vaccination programs and 17 studies reported vaccine effectiveness (direct effect) of MCCV. Studies came from 9 different countries; 11 from England and Wales/UK [20][21][22][23][24][25][26][27][28][29][30], 10 from Spain [31][32][33][34][35][36][37][38][39][40], 5 from Canada [41][42][43][44][45], 4 each from Brazil [46][47][48][49] and Italy [50][51][52][53], 2 each from Australia [54,55] and the Netherlands [56,57], and one each from Germany [58] and Belgium [59]. The MCCV were introduced as part of the routine childhood NIP in all these countries.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the overall number of cases caused by non-B serogroups, increased during the study period. In particular, an increase in cases of IMD related to serogroups Y and W was described [ 40 , 41 , 48 ], whereas serogroup C was almost s from 2012 to 2014, increasing in 2015 and 2016 [ 40 , 43-45 ]. This epidemiological evidence, as well as the possibility of capsular switch from one serogroup to another [ 12 , 18-22 ], should lead the national decision makers to boost the use of the MenACWY vaccine instead of MenC in the next PNPV, as already done in Emilia-Romagna [ 49 ], Apulia [ 50 ] and Sicily [ 51 , 52 ] and recently implemented in other countries [ 53 , 54 ], to ensure more comprehensive protection.…”
Section: Discussionmentioning
confidence: 99%